SEASONAL DYNAMICS OF ALGOFLORA TAXON OF THE NORTH FERGANA CHANNEL (Scientific journal of the Fergana State University, 2023)
In this article, the changes in the diversity of taxa in the algoflora developed in the Northern Fergana canal under the influence of environmental factors, their taxonomic composition and biological diversity in water bodies, including the systematic composition of the taxa that make up the algoflora, changes that occur under the influence of ecological factors during the seasons information about the connection with a number of biotic and abiotic factors.